2012
DOI: 10.1007/s00296-012-2394-4
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of p-coumaric acid, a common dietary phenol, on adjuvant-induced arthritis in rats

Abstract: p-Coumaric acid (3-(4-hydroxyphenyl)-2-propenoic acid), a common dietary polyphenol, is widely distributed in cereals, fruits and vegetables with antioxidant property. Numerous studies have enlightened the ability of dietary phenols to be considered as potential therapeutics against arthritis. In this study, we aimed to investigate the ameliorative effect of plant phenolic p-coumaric acid on adjuvant-induced arthritis in rats. The reference drug indomethacin was used for comparison purposes. Arthritis was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…As previous studies have unravelled ameliorative properties such as anti‐ulcer , anti‐microbial , anti‐platelet , anti‐mutagenic , and anti‐inflammatory activities ; making CA an ideal natural compound to elucidate further against RA. Recently, we showed that the anti‐peroxidative and lysosomal membrane‐stabilizing effect of CA in adjuvant‐induced arthritic rats . Here, we validated the anti‐arthritic effect of CA and explored its underlying molecular mechanism in the in‐vivo and in‐vitro model.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As previous studies have unravelled ameliorative properties such as anti‐ulcer , anti‐microbial , anti‐platelet , anti‐mutagenic , and anti‐inflammatory activities ; making CA an ideal natural compound to elucidate further against RA. Recently, we showed that the anti‐peroxidative and lysosomal membrane‐stabilizing effect of CA in adjuvant‐induced arthritic rats . Here, we validated the anti‐arthritic effect of CA and explored its underlying molecular mechanism in the in‐vivo and in‐vitro model.…”
Section: Introductionmentioning
confidence: 85%
“…The drugs (1 ml) were administered intraperitoneally on day 11 to day 26 consecutively for 16 days. The dosage of CA was fixed based on the preliminary results . DEXA scan was carried day 0 (before the onset of symptoms), day 11(after the onset of symptoms), and day 27(prior to sacrifice).…”
Section: Methodsmentioning
confidence: 99%
“…The hydroxycinnamic (a) and the hydroxybenzoic (b) acids, are two main groups of phenolics; (a) group contains caffeine, ferulic and p-coumaric acids, but the (b) group contains gallic, protocatechic acids [97,98]. p-Coumaric acid is the stepping stone in synthesis process of caffeic, chlorogenic and ferulic acids, and these phenolics lead to have an antimicrobial and antiviral effects in different mode of actions as it could kill the fungal and bacterial cells by breakdowns and ruptures the plasma membrane [99][100][101][102][103]. In another study, the cinnamic acid proved to be effective in suppressing the virulent species of Pectobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…It is a major precursor in the synthesis of other phenolic acids, such as caffeic, chlorogenic, rosmarinic and ferulic acids. It is widely distributed in fruits, vegetables, cereals and mushrooms [ 22 , 23 ]. Studies on p -coumaric acid and its conjugated forms revealed properties, such as antioxidant, antimicrobial, antitumor, anti-inflammatory, antiplatelet aggregation, as well as other interesting health benefits [ 24 ].…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 99%